2022
DOI: 10.3390/cancers14194610
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Insufficiency with Anticancer Tyrosine Kinase Inhibitors Targeting Vascular Endothelial Growth Factor Receptor: Analysis of the FDA Adverse Event Reporting System

Abstract: Background: We described clinical features of adrenal insufficiency (AI) reported with tyrosine kinase inhibitors (TKIs) targeting vascular endothelial growth factor receptor (VEGFR) in the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Reports of AI recorded in FAERS (January 2004–March 2022) were identified through the high-level term “adrenal cortical hypofunctions”. Demographic and clinical features were inspected, and disproportionality signals were detected through the Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Moreover, our consolidated analysis (comparing the signals of TLS between mAbs and other anticancer drugs for MM) indicated that all mAbs presented an increased disproportionate signal for TLS. We adopted the adjusted Bradford Hill Criteria from previous publications 33 and then assessed the link between TLS and mAbs point‐by‐point. Although it is impossible to build up a causal relationship between a specific drug and an AE only by using disproportionality analysis from the FAERS database without a proper review of the individual case reports, our results do show that mAbs may increase the potential of TLS in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our consolidated analysis (comparing the signals of TLS between mAbs and other anticancer drugs for MM) indicated that all mAbs presented an increased disproportionate signal for TLS. We adopted the adjusted Bradford Hill Criteria from previous publications 33 and then assessed the link between TLS and mAbs point‐by‐point. Although it is impossible to build up a causal relationship between a specific drug and an AE only by using disproportionality analysis from the FAERS database without a proper review of the individual case reports, our results do show that mAbs may increase the potential of TLS in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…A causal relationship assessment was carried out on the entire body of evidence by using adapted Bradford Hill Criteria used in epidemiology that have been applied to pharmacovigilance data, 33 including biological plausibility, strength, consistency, specificity, coherence, and analogy. The rechallenge/de‐challenge item were not analyzed in this study due to missing data.…”
Section: Methodsmentioning
confidence: 99%
“…This study adopted novelty of the drug event association, seriousness, and disproportionate reporting as criteria for the signal prioritization. Moreover, a causal relationship appraisal was carried out on the entire body of evidence by using adapted Bradford Hill criteria used in epidemiology that have been applied to pharmacovigilance data ( van Hunsel et al, 2018 ; Raschi et al, 2022 ), including biological plausibility, strength, consistency, specificity, coherence, and analogy. The rechallenge/de-challenge item were not analyzed in this study due to missing data.…”
Section: Methodsmentioning
confidence: 99%
“…Immune checkpoint inhibitors may be associated with endocrine abnormalities in 25–50% of individuals on these medications [ 8 ]. Tyrosine kinase inhibitors targeting the vascular endothelial growth factor receptor have also been associated with adrenal insufficiency [ 235 ].…”
Section: Organ-specific Inflammatory Diseasesmentioning
confidence: 99%